Порушення та крадіжки при споживанні природного газу - Хомич, Д.; Khomych, D. (Східноєвропейський національний університет імені Лесі Українки, 2017)
В статті подано способи втручання в роботу газових лічильників та відповідальність, яка передбачена законом за такі порушення. Наголошується, що втручання в роботу лічильників залишаються найпопулярнішим видом крадіжки газу, який становить 70% від виявлених серед споживачів порушень. На сьогодні є цілий ряд методів відмотування або зупинки газового лічильника. The legislation regulating the use of gas, control and legal responsibility for infractions of the established procedure include: the Law of Ukraine «On Metrology and Metrological Activities», the Code of Gas Distribution Systems, the Criminal Code of Ukraine, the Order «On Approval of the Regulation on the Examination of Gas Meters Established by Consumers and intended for the account of natural gas in a household». The article presents the ways of interferes in the work of gas meters and the liability that is provided by law for such infractions. A number of methods of winding, stopping and other illegal manipulations with gas meters are considered. Recommendations on the methodology for identifying and fixing interventions in the work of gas meters to bring the perpetrators to legal liability for such violations are also shown.
Infractions and Theft in the Sphere of Using of the Natural Gas
Keywords: втручання в роботу лічильника; несанкціонований відбір природного газу; крадіжка газу; юридична відповідальність; intervention in the meter operation; unauthorized gas selection; gas theft; legal responsibility; 343.3.7